Arkæologen Erik Westerby – Frontforsker på fritidsbasis - Fischer, Anders (Kuml, 2002)
The archaeologist Erik Westerby Up-front researcher on a spare-time basis The centenary of the archaeologist and lawyer Erik Westerby, born in 1901, is the occation of this ac count of his career. It is a tale of a talented person’s magnificent achievements in his vainly fight for a seat on the scientific Parnassos. Erik Westerby had out standing intellectual talents within more of the areas important for car ying out a rchaeological research at a high level. Initially, however, a youthful and ill-concealed belief in his own talents gave him problems getting on with the conservative research environment of his contemporaries. In addition he had to struggle with a complicated mind of his own. From his youth, Westerby’s dedication to archaeology was directed to the exploration of the oldest times. He was the first to present a settlement from the late Ice Age: the Bromme site, and until today he has remained one of the famous names within the early Stone Age research in Denmark. His mind was set on archaeology, and yet he chose a more sec ure way of earning a living and became a lawyer. Parallel to the law studies, he worked so vigorously with archaeology that it is difficult to understand how he managed to graduate with good marks in an extraordinarily short time. In 1929, he settled as an independent lawyer in Copenhagen, in an office close to the High Court and the National Museum. The Stone Age settlement of Bloksbjerg in northern Copenhagen was the object of Westerby’s first large-scale field work (fig. 1). Nineteen years old, he published the preliminary results of the excavation.The following year he extended his knowledge of the Palaeolithic Period of France during a one-month study visit in Dordogne, an area rich of archaeologi cal finds.These studies were carried out with great thoroughness and included carefully documented test excavations at some of the classical sites. When he was 26, Westerby published a thesis on the early Stone Age in Denmark, taking his own settlement investigations as his point of departure. In this book, the term “the Mesolithic Age” was introduced in Danish terminology. Here, he also argued for the individual culture eras being named after important find localities. The early part of the Mesolithic Age in Denmark (which prior to this was often called “the Bone Age”) was hence to be called the Maglemose Era and the late part the Ertebø1le Era.The local academic dignit aries met this termino logy with severe criticism. Nevertheless, it was gradually accepted far beyond the Danish borders. From a modern point of view, the book was a very com etent archaeological presentation. It was submitted to the University of Copenhagen as a dissertation. However, the established scholars showed their disapproval by simply rejecting it. To add insult to injury, the promising youth was even humiliated in public by members of the National Museum’s staff. Among other things they pounced on the claim that a widely occurring, yet hitherto unnoticed type of flint tool, the burin, was to be found in the settlement inventories of the early Stone Age in Denmark. Today, we all know that Westerby was right, but in the 1920s, this claim was received differently by the few professional archaeologists in Denmark. Westerby was considered unsuited as a professional archaeologist, and so his profession was to stay the law. His next large project was the testing of the theory that coastal settlement had existed before the Ertebø1le Era Through reconnaissance expeditions to reclaimed fiords, he established co mpr ehensive traces of coastal settlement from a time berween the Ertebølle Culture and the Maglemose Culture. This era is now called the Kongemose Era, but it could just as well have been called the “Gislinge Era” due to his rich settlement find of this era in the Lamme fiord in North-West Zealand. However,Westerby decided to play down the sigruficance of his new find and refrain from such a pretentious terminology. In 1933, the results of Erik Westerby’s investigations of the reclai med fior ds were published. The energetic, Stone Age knowledgeable Therkel Mathiassen, who was employed by the National Museum that year, was interested in the Gislinge site, but he did not get an opportunity of excavating it until seven years later. And this was not to be the last place where Westerby’s and Mathiassen’s paths crossed. Erik Westerby’s next large project was to find signs of late Ice Age settlements in Denmark – until then, this era was on ly represented by stray items. To do this, he carried out comprehensive field reconnaissance, which among other things led to his arrest by both the Danish police and the German occupying power due to his unu sual activities in the landscape. In 1938, he realised that the Amose bog in Western Zealand was a true treasure chest when it came to Mesolithic settlements. This realisation led to a short article in the reputable scholarly magazine , Acta Archaeologica. The article presents the results of a small trial excavation on the Øgårde locality. Having expressed reservations due to the limited and provisional character of the investigation, he concluded that there were pottery sherds in a closed context from the Maglemose Era, and that this was therefore the hitherto oldest pottery find in the world (fig. 2). Westerby called on the National Museum to undertake the responsibility of further investigation into the Åmose settlements, and Therkel Mathiassen immediately took it up on himself to take care of it. When a few years later he published the results of his very comprehensive investigations of for instance Øgårde, the sensational (and wrong) conclusion, that the Maglemose culture knew how to make pottery, was maintained. From Westerby’s diary we know that at the age of thirty, he regretted having been induced to deal with law. Archaeology fascinated him much more, and here he had exceptional talents. In private, he was a lonely person, and his legal work suffered from his great commitment to archaeology.The striking gesture of handing over further work concerning the Åmose settlements to the National Museum may therefore be understood as an attempt to get out of aneconomically, socially, and professional dead end. He probably hoped that the museum would encourage him to carry on the investigations and that he would be given the necessary means to do so – perhaps in the form of permanent employment. If indeed such hopes were behind Westerby’s gesture, then they were completely ignored. Therkel Mathiassen left him no further possibilities of carrying on the work in Åmosen. He even walked on Westerby’s pride by publicly mentioning him in line with local artefact collectors, who helped the museum with its work in the bog. However, Westerby continued his systematic field reconnaissance elsewhere on Zealand. In the spring of 1944, on the edge of a bog near Bromme, northwest of Sorø, he found flint tools of a kind that made him conclude he had come across settlement traces from a late Ice Age settlement (fig. 4, 6, and 7). The National Museum quickly offered to help with the investigation. However, the sensatio al find had disturbed Westerby’s state of mind, and he declined the proposal for fear of Mathiassen (fig. 5) taking over the management of the investigations. Physical and mental over-exertion caused Westerby to seek medical treatment in the autumn of 1944 . As he had no recovered by the spring of 1945, he informed the National Museum of the situation and turned over further investigation to the museum. His approach to the museum was an unspoken request that he was given the possibility of leading the investigation against proper payment. However, the signal was ignored, and Mathiassen immediately began the planning of a large-scale investigation. Westerby inspected the investigatio , and a written controversy followed, in which he expressed his reservations about Mathiassen’s methods, interpretations, and professional ethics, before having a mental relapse. Westerby’s miserable mental and economical situation now caused his sister, Hjørdis Westerby, to contact the National Museum , and without her brother’s knowledge, she expressed his wish of a museum employment, which for years he had been too proud to express. A marked change in the museum’s course followed. Therkel Mathiassen wrote and offered Erik Westerby a favourable arrangement. Westerby answered,“The letter will be opened, read, and if necessary answered when my health and my doctor permits it”. Whether Westerby ever opened the letter is unknown. The following spring Mathiassen wrote another couple of letters in his new, generous manner. The latter of these was found unopened among the papers left behind by Westerby. The good initiative had come too late. In the spring of 1946, Erik Westerby, helped by his sister Hjørdis, wrote a scholarly presentation of his investigations of the Bromme settlement.The manuscript included remarks that could be easily interpreted as a critical comment on the National Museum. As Westerby did not want to delete them, the result was that he never saw the presentation published in its entirety. Mathiassen published his results from the site in a large article in 1948. A later reinvestigation of the complete find material from the site has shown that Westerby’s critical remarks on Mathiassen’s methods and interpretations were justified. I t is worthy of note that not only did Westerby find the Bromrne settlement; he also recognized the finds on this site as being from the late Ice Age. Later it has become evident that Bromme was not the first late Palaeolithic settlement to be found or published withom the archaeologists realizing the correct age of the artefacts. In the last months of 1946, Erik Westerby left Copenhagen in order to become a member of the legal staff on the police station in Ringkøbing, West-Jutland. In his spare time, he continued to cultivate his interest in archaeology. He gave himself the extreme task of finding traces of human habitation in Denmark prior to the last Ice Age. A gravel pit near Seest in the western part of Kolding especially attracted his attention. Here, remains from for instance rhinoceros and forest elephant were found in the melt water gravel from the Ice Age. The gravel pit finds included some man- made flint items, which may be from the Ice Age layers. At that time,Westerby’s professional competence finally gained unreserved acclaim. The then recently appointed leader of the Prehistoric Museum in Århus, professor P.V. Glob, was behind this. Among other things, he arranged Westerby’s participation as a Danish represent ative in an international congress to mark the centenary of the find of the famous Neanderthal skull (fig. 8). In Ringkøbing, Westerby gradually became a known figure (fig. 9), and his extraordinary housing conditions added considerably to his reputation as an eccentric – a status he seemed to cultivate with pleasure (fig. 11-12).When he first arrived in the town, he was assigned one of the more modest rooms in the local hotel. Here he stayed for 33 years! Erik Westerby’s eccentric personality may lead to the convenient conclusion that he was unsuited for anemployment at the National Museum. It should therefore be stressed that he functioned as a highly respected police official in Ringkøbing (fig. l0) until according to the state rules he was forced to retire at the age of 70. The story of Erik Westerby’s professional career inevitably casts a shadow over those archaeologists at the National Museum who were actively opposing him. And it must be emphasized that the negative appraisal should not just apply to the rank-and- file scholars, but also the leading profession als, who failed to create the possibilities for Westerby’s obvious talents to be exploited to the full. Each scholarly environment should be conscious of the fact that success does not just depend on the available economic resources. The profession’s ability to provide a breeding ground for new ideas and gifted persons – even when this seems to be conflicting the individual convenience a nd prestige of established scholars – is no less important. If the management is weak and lacking in visions, then the environment tends to pursuit in dividu l goals. The result is often a bad atmosphere. It is a common idea that lack of funds causes lack of constructive athmosphere. However, it may just as well be the lack of constructive athmosphere, which causes lack of funds. Danish archaeology is indebted to Erik Westerby for handing over the key localities for investigating the Early Stone Age, and for his instructive examples in methods and systematism. We are also indebted to his sister, Hjørdis Westerby,for showing our profession a great gesture after the death of her brother: due to her economy and business sense, she was able to found the Erik Westerby Foundation in support of Danish archaeologists. The capital of the foundation comes from the estate left by her brother and from a large gift of money from her. Anders Fischer Kulturarvsstyrelsen Translated by Annette Lerche Trolle